Multitasking at work: Do firms get what they pay for? - Ann P. Bartel (IZA World of Labor, 2017)
To align employees' interests with the firm's goals, employers often use performance-based pay, but designing such a compensation plan is challenging because performance is typically multifaceted. For example, a sales employee should be incentivized to sell the company's product, but a focus on current sales without rewarding the salespeople according to the quality of the product and/or customer service may result in fewer future sales. To solve this problem, firms often increase the number of metrics by which they evaluate their employees, but complex compensation plans may be difficult for employees to understand.
Keywords: J33; 330; incentives; multitasking; gaming; balanced scorecard